2019
DOI: 10.1074/jbc.ra119.009960
|View full text |Cite
|
Sign up to set email alerts
|

NECA derivatives exploit the paralog-specific properties of the site 3 side pocket of Grp94, the endoplasmic reticulum Hsp90

Abstract: The hsp90 chaperones govern the function of essential client proteins critical for normal cell function as well as cancer initiation and progression. Hsp90 activity is driven by ATP, which binds to the N-terminal domain and induces large conformational changes that are required for client maturation. Inhibitors targeting the ATP-binding pocket of the N-terminal domain have anticancer effects, but most bind with similar affinity to cytosolic Hsp90␣ and Hsp90␤, endoplasmic reticulum Grp94, and mitochondrial Trap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 41 publications
(50 reference statements)
0
24
0
Order By: Relevance
“…Our compound 4 bears an adenosine moiety (FIG. 7), shared by GRP94-selective inhibitor NECA, 40 that binds to the ATP binding site. Additionally, NECA was also shown to interact with Site 3 of GRP94.…”
Section: Discussionmentioning
confidence: 99%
“…Our compound 4 bears an adenosine moiety (FIG. 7), shared by GRP94-selective inhibitor NECA, 40 that binds to the ATP binding site. Additionally, NECA was also shown to interact with Site 3 of GRP94.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, it has been shown that the small differences in amino acid sequences resulted in some structural variations between Hsp90 proteins from different organisms and in different cellular compartments [ 111 ]. The elucidation of several Hsp90 crystal structures has provided more avenues to identify drug targets based on unique conformations of the Hsp90 proteins [ 112 ]. These structural insights gained from the high-resolution crystal structures have led to the screening and identification of novel Hsp90 inhibitors.…”
Section: P Falciparum Hsp90 As Drug Targetsmentioning
confidence: 99%
“…This leads to a loss of membrane potential and the release of cytochrome c, resulting in selective cancer cell apoptosis [ 150 , 152 ]. Another purine-scaffold Hsp90 paralog selective inhibitor of Grp94, N-ethyl-carboximido adenosine (NECA), was identified ( Figure 7 ) [ 112 , 113 ]. The selectivity of NECA and its derivatives N-propylcarboxamido adenosine (NPCA), N-hydroxyethylcarboxamido adenosine (NEoCA), and N-aminoethycarboxamido adenosine (NEaCA) [ 112 ] for Grp94 are based on the N-ethyl carboximido moiety that extends into the third hydrophobic pocket that surrounds the ATP binding pocket of Grp94.…”
Section: P Falciparum Hsp90 As Drug Targetsmentioning
confidence: 99%
See 2 more Smart Citations